Analyzing Student Problem-Solving With MAtCH - Chiu, Barbara; Randles, Christopher; Irby, Stefan (Frontiers in Education, 2022)
Problem-solving has been recognized as a critical skill that students lack in the current education system, due to the use of algorithmic questions in tests that can be simply memorized and solved without conceptual understanding. Research on student problem-solving is needed to gain deeper insight into how students are approaching problems and where they lack proficiency so that instruction can help students gain a conceptual understanding of chemistry. The MAtCH (methods, analogies, theory, context, how) model was recently developed from analyzing expert explanations of their research and could be a valuable model to identify key components of student problem-solving. Using phenomenography, this project will address the current gap in the literature of applying the MAtCH model to student responses. 22 undergraduate students from first-year general chemistry and general physics classes were recorded using a think-aloud protocol as they worked through the following open-ended problems: 1) How many toilets do you need at a music festival? 2) How far does a car travel before a one atom layer is worn off the tires? and 3)What is the mass of the Earth's atmosphere? The original definitions of MAtCH were adapted to better fit student problem-solving, and then the newly-defined model was used as an analytical framework to code the student transcripts. Applying the MAtCH model within student problem-solving has revealed a reliance on the method component, namely using formulas and performing simple plug-and-chug calculations, over deeper analysis of the question or evaluation of their work. More important than the order of the components, the biggest differences in promoted versus impeded problem-solving are how students incorporate multiple components of MAtCH and apply them as they work through the problems. The results of this study will further discuss in detail the revisions made to apply MAtCH definitions to student transcripts and give insight into the elements that promote and impede student problem-solving under the MAtCH model.